2017
DOI: 10.3945/cdn.116.000299
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Protein Intake Is Associated with Insulin Resistance in Adventist Health Study 2 (AHS-2) Calibration Substudy Participants: A Cross-Sectional Analysis

Abstract: Background: High intakes of total and animal protein are associated with the risk of type 2 diabetes (T2D). The influence of protein type on insulin resistance, a key precursor of T2D, has not been extensively studied. Objective: The aim of this study was to determine the associations between dietary total, animal, and plant protein intakes as well as the animal-to-plant protein (AP) intake ratio with insulin resistance in middle-aged and older adults. Methods: This was a cross-sectional analysis in 548 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 54 publications
4
22
2
2
Order By: Relevance
“…Thus, not a high protein intake in general but the protein quality may play a crucial role for modulating disease risk [ 16 , 17 ]. This is in line with other studies showing that not the total protein intake itself but the protein composition or the AA pattern is important with regard to risk of T2D and CVD [ 37 , 38 , 39 ]. These results strengthen our hypothesis that the dietary pattern beyond the intake of BCAA rather than the effect of BCAA intake itself contribute to the increased risk for chronic diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, not a high protein intake in general but the protein quality may play a crucial role for modulating disease risk [ 16 , 17 ]. This is in line with other studies showing that not the total protein intake itself but the protein composition or the AA pattern is important with regard to risk of T2D and CVD [ 37 , 38 , 39 ]. These results strengthen our hypothesis that the dietary pattern beyond the intake of BCAA rather than the effect of BCAA intake itself contribute to the increased risk for chronic diseases.…”
Section: Discussionsupporting
confidence: 92%
“…The current study split total dietary protein intake into AP and PP intake. Contrary to other reports of an increased risk of GDM in a pregnant population [9,12,42,43,44], and increased insulin resistance in a non-pregnant population [24], we did not find any prominent relationship between maternal AP intake and insulin sensitivity. It is notable that in spite of lack of such a relationship, there still was a positive connection between TP and PP intake and insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of long-term higher protein diets on insulin regulation and glucose metabolism is less clear with some studies reporting a negative effect, and others reporting a neutral or positive effect [8,16,17,18,19,20,21,22,23]. Further, the source of the dietary protein may impact insulin regulation and glucose metabolism with studies supporting a negative impact of animal sources (specifically red meat and processed meat) [24,25], and a positive impact of plant-based and lean animal meat sources [25,26]. These relationships in a pregnant population are unclear due to the limited amount of data.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, are plant-derived proteins healthier than animal proteins? Protein intake studies in humans have suggested that whilst high intake of animal proteins has a negative effect on metabolic health, this may not be the case for vegetable protein intake (Azemati et al, 2017; Sluijs et al, 2010). Indeed, clinical trials of vegan diets have found that they promote metabolic health, although the lower levels of proteins consumed by many vegans is a confounding factor (Barnard et al, 2009, 2006; Lee et al, 2016).…”
Section: Amino Acids Act As Metabolic Health Regulatorsmentioning
confidence: 99%